Pigmented maize - a potential source of β-carotene and α-tocopherol - Violeta, Anđelković; Mesarović, Jelena; Srebrić, Mirjana; Mladenović Drinić, Snežana (Journal of Engineering & Processing Management, 2018)
Among cereals, maize has the highest content of bioavailable micronutrients in grain, particularly β-carotene and α-tocopherol, which makes this crop the most appropriate for biofortification. Great genetic variability is a valuable source of micronutrients, and genotypes with enhanced grain content could be used for improvement of commercial hybrids or synthetic populations creation. Three populations with dark orange, dark red and red grain, five elite lines, and their crosses were evaluated for β-carotene and α-tocopherol content. Based on obtained results, line (L5) could be further used in breeding for increased β-carotene content, and population with dark orange grain (P1) is recommended as a good source for multi-nutrient biofortification for both β-carotene and α-tocopherol. Three lines (L1, L2 and L5) had significantly higher value of α-tocopherol in crosses with dark red population (P2), compared to lines per se, and require several cycles of back-crossing for increase nutrient content.